Microstructure and properties of titanium-based materials promising for antiballistic protection - Ivasishin, О.М.; Markovsky, P.E.; Savvakin, D.G.; Stasiuk, O.О.; Golub, V.A.; Mirnenko, V.І.; Sedov, S.H.; Kurban, V.А.; Antonyuk, S.L. (Успехи физики металлов, 2019)
Titanium-based materials, which combine high strength and hardness of surface layer along with sufficient ductile characteristics of the matrix metal, are very promising for various applications, particularly, as armoured components in military-industrial complex. Above-mentioned combination of properties can be achieved by means of the creation of multilayer structures, which consist of layers possessing different physical and mechanical properties. In the present study, microstructure peculiarities, mechanical and antiballistic protection properties of the layered Tibased materials are investigated. Two different ways were used for fabrication of such the layered structures. Титанові матеріaли, які поєднують високу міцність і твердість поверхні при достатніх пластичних характеристиках основного металу, є перспективними для використання в різних галузях техніки, зокрема, в якості бронеелементів у військово-промисловому комплексі. Одержати вищевказану комбінацію властивостей можливо, створюючи матеріaли, які складаються з декількох шарів, що відрізняються за своїми фізико-механічними характеристиками. В роботі досліджено особливості мікроструктури, механічних характеристик і балістичної стійкості таких матеріaлів, створених за двома підходами. Титановые материалы, которые совмещают высокую прочность и твёрдость поверхности при достаточных пластических характеристиках основного металла, являются перспективными для использования в различных областях техники, в частности, как бронеэлементы в военно-промышленном комплексе. Достичь такой комбинации свойств возможно, создавая материалы, состоящие из нескольких слоёв, которые отличаются по своим физико-механическим характеристикам. В работе исследованы особенности микроструктуры и механических характеристик таких материалов, созданных двумя путями.